Soulidarity with Universality: The Call of the Time Spiritual Relationality as the Blueprint for Planetary Evolution - Dr Aneeqa Malik (South Asian Journal of Religion and Philosophy (SAJRP), 2025)
This article recounts my experiential engagement with the Call of the Time (COTT) dialogue, a collaborative initiative between the Brahma Kumaris (BK) and Minhaj University Lahore’s Shaykh-ul-Islam Spiritual Studies Centre (SISS), facilitated by the Department of Religion and Philosophy. Framed within Brahma Kumaris’ cyclical cosmology and SISS’s mission to synthesise Islamic spirituality with contemporary challenges, the event exemplified the potential of inter-spiritual dialogue to transcend sectarian boundaries within Pakistan as observed through the varied inter-faith participation. As a fellow of the Inayatiyya Universal Sufi Order a lineage founded by Hazrat Inayat Khan to synthesise Sufi mysticism with universal spirituality I participated in this dialogue to explore resonances between my own tradition’s emphasis on Tawhid (Divine Unity) and the Brahma Kumaris’ (BK) teachings on soul consciousness and cyclical time. Through thematic analysis, this study explores how the convergence of Sufi universalism (as articulated by Pir Zia Inayat-Khan, grandson of Hazrat Inayat Khan) and BK teachings on soul consciousness can foster a transformative space for socio-spiritual renewal to address humanity’s existential crises locally and globally. Additionally, by articulating the concept of “Soulidarity with Universality,” the study argues that inner spiritual transformation manifested through meditative practices and reflective discourse can catalyse collective social renewal when understood as an expression of spiritual relationality. The discussion is contextualised within contemporary challenges of social disconnection and the limitations of conventional interfaith dialogue in Pakistan, suggesting that a socio‐spiritual integration model rooted in relational engagement offers a promising path toward societal transformation. Key themes include the dissolution of artificial binaries between inner transformation and social action, the amplification of spiritual relationality beyond interfaith paradigms, and the implications of such dialogues for fostering global solidarity.